Impact of Public Debts Accumulation on Economic Growth in Nigeria: Issues and Implications for Economic Recovery - Eze, Titus Chinweuba; Ukwueni, Nnaemeka Ole (ABUAD Journal of Social and Management Sciences, 2023)
This paper interrogates the rationale behind federal government continued reliance on Keynesian’s fiscal policy prescriptions of deficit financing as a way of spurring sustained economic growth and development in Nigeria, especially when such ideology seems to contrast sharply with the realities of dwindling economic growth indices. In particular, this study investigates the extent both external debt and domestic debt impact on economic growth in Nigeria. Multiple regression method was adopted while Autoregressive distributed lag (ARDL) model was the main technique used in the analysis. The results of the ARDL model demonstrate that external debt (LEXD) and domestic debt (LDD) have a negative impact on LGDP. However, while external debt reveals a significant effect, domestic debt (LDD) has an insignificant impact on LGDP. Thus, the study recommends that government should discontinue the use of external debt to finance budget deficit in the economy, but look inward through aggressive internal revenue generation as well as embrace economic diversification policies, coupled with a drastic cut down on cost of governance in Nigeria.